Impact of waterlogging stress on juice quality in sugarcane cultivated in tropical India - R. Gomathi; K.Chandran; R. Arun Kumar; Alagupalamuthirsolai M; V. Krishnapriya (Journal of Sugarcane Research, 2023)
Juice quality and nutrient status were studied in different maturity stages of 16 sugarcane clones under normal and water-logged conditions in two cropping seasons. In both the cropping seasons, the brix of juice showed an increasing trend towards maturity (18.78 to 20.23%), while sucrose content in juice reached its maximum in the 11th month (17.78%) and declined in the 12th month (16.71%). Reducing sugar varied from 0.45 to 2.15%, and out of 16 clones studied, seven recorded less than 1.0% reducing sugars under water logged conditions. The clones that showed higher brix and sucrose content registered lesser values of reducing sugars and vice-versa. Juice electrical conductivity varied from 0.90 (88 WL 2137 and 98 WL 1357) to 1.80 (88 WL 1072), while pH of the juice did not show signiﬁcant variation among clones. Under water logging conditions, nitrogen and potassium content in juice signiﬁcantly varied among the clones, while phosphorous content did not show signiﬁcant variation. In both planting seasons, the clones WL 1061, 92 WL 1029, 93 WL 1297, 97 WL 633, 99 WL 379, and 91 WL 629 recorded comparatively better juice quality parameters under water logged conditions similar to that of resistant standards (Co 62175 and Co 8231).